Total Communication as the Basis for the Learning Preparation Programs of Deaf Student - Grahita Kusumastuti; Iga Setia Utami (Universitas Muhammadiyah Enrekang, 2023)
This study aims to describe the total communication training model as the basis skill for preparing a learning program for deaf students. This model development is conducted by compiling the concept of total communication training through discussion. The results of the discussion are then developed in terms of material and technical implementation. The training model implemented and measured its effectiveness in terms of improving the ability of teachers to compile learning programs based on the type of student communication using a total communication approach. The results show that the concept of seminars and workshops in training is very effective in improving the ability of teachers to compile learning programs for deaf students that are tailored to their communication characteristics.